CHARACTERISTICS OF SUGARCANE JUICE AND YOUR INFLUENCE IN THE BEVERAGE STABILITY - PRATI, PATRICIA; CAMARGO, GISELE ANNE (Revista Brasileira de Engenharia de Biossistemas, 2008)
Brazil is considered to be the major world producer of sugar cane, and the South-Eastern and North-Eastern regions of Brazil are the main national producers. The aim of this study was to determine the principal constituents of sugar cane juice as water, saccharose, reducent sugars, protein, total polisaccharides, dextran, ash and minerals (phosphorus, potassium, calcium and magnesium) and carry out physical-chemical determinations (pH, acidity, soluble solids, ascorbic acid content and pectinesterase activity). For the same reason, the following microbiological analyses were carried out: standard total count, total and fecal coliforms, mold and yeast count. The constitu-ents determined were: water, sucrose, reducing sugars, protein, total polysaccharides, dextran, ash and minerals such as phosphorus, potassium, calcium and magnesium. The determinations showed that sugar cane juice is a beverage extremely rich in sugars, which together with its pH, make it a highly perishable product, that needs a conservation process. Since the constituents of the juice are all present in low concentrations, clarification should not be a problem. The sugar cane juice isn't a good source of ascorbic acid. The microbiological conditions of natural beverage were considered good.